2009
DOI: 10.2298/avb0903193k
|View full text |Cite
|
Sign up to set email alerts
|

The comparative evaluation of serum biochemical, haematological, bacteriological and clinical findings of dead and recovered bitches with pyometra in the postoperative process

Abstract: The aim of this study was to investigate the prognosis, the risk status and the death reasons in dead and recovered bitches with pyometra after the operative approach by comparing serum biochemical, and haematological parameters, as well as bacteriological and clinical findings. Bitches with pyometra (n=30) were ovariohysterectomized. Eight bitches that died after the ovariohysterectomy formed Group 1 and the rest, which recovered, was Group 2. In addition, 10 healthy bitches were used as the reference for hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Most bacteria isolated from uterine content are gram negative bacteria that release lipopolysaccharidestructured endotoxin from their cell walls [1,3,5] . Multiple organ failure due to sepsis [6] and death may be observed in this disease [7][8][9] . Previous studies have shown that the mortality rate caused by pyometra is about 4-26% [7,9,10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most bacteria isolated from uterine content are gram negative bacteria that release lipopolysaccharidestructured endotoxin from their cell walls [1,3,5] . Multiple organ failure due to sepsis [6] and death may be observed in this disease [7][8][9] . Previous studies have shown that the mortality rate caused by pyometra is about 4-26% [7,9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple organ failure due to sepsis [6] and death may be observed in this disease [7][8][9] . Previous studies have shown that the mortality rate caused by pyometra is about 4-26% [7,9,10] . Renal dysfunction and hepatocellular damage caused by septicemia and/or diminished hepatic circulation and cellular hypoxia in a dehydrated bitch can lead to alteration in variety of serum biochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There were 44 eligible publications (Llazani et al n.d., de Schepper et al 1987, van Bree et al 1988, Fransson et al 1997, Faldyna et al 2001, Nak et al 2001, Fransson 2003, Fransson et al 2004, Hagman et al 2006a,b, Fransson et al 2007, Kilinç 2008, Hagman et al 2009, Küplülü et al 2009, Hagman 2011, Emanuelli et al 2012, Karlsson et al 2012, Radwińska et al 2012, Patil et al 2013, Sharif et al 2013, Ambrosen 2014, Enginler et al 2014, Jitpean et al 2014, Klainbart et al 2014, Voorwald et al 2015, Dąbrowski et al 2015a, 2015b, Gultiken et al 2016, Karabulut et al 2016, Karlsson et al 2016, Lidén 2017, Karabulut & Sonmez 2018, Tecles et al 2018, Alkan et al 2020, Gasser et al 2020, Hadiya et al 2020, Koenhemsi et al 2020, Maharathi et al 2020, Pugliese et al 2020, Ahn et al 2021, Günay Uçmak et al 2021…”
Section: Study Characteristics and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Elevated levels of blood urea nitrogen (BUN) and serum creatinine in the ovariohysterectomized bitch were linked to higher postoperative mortality rates (Kuplulu et al, 2009). Further, progression of pyometra into sepsis and elevated serum creatinine levels were linked to extended hospital stays, mortality, or both (Sant'Anna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies emphasize the importance of clinical evaluation of bitches with pyometra to make any decision for treatment and hospitalization, chances of post‐treatment complications and mortality (Hagman, 2012; Jitpean et al, 2014; McCallin et al, 2021). Elevated levels of blood urea nitrogen (BUN) and serum creatinine in the ovariohysterectomized bitch were linked to higher postoperative mortality rates (Kuplulu et al, 2009). Further, progression of pyometra into sepsis and elevated serum creatinine levels were linked to extended hospital stays, mortality, or both (Sant'Anna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%